2015
DOI: 10.1149/2.0081511jss
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Linear Aliphatic Polyamines on Copper Removal Rate in Chemical Mechanical Planarization (CMP)

Abstract: The role of homologous linear aliphatic polyamines as additives in Cu CMP slurries was investigated. We show that, in addition to forming stable complexes with copper ions in solution, the polyamines also interact with the copper metal preventing its corrosion. The latter effect increases with the polyamine chain length making the superior members of the homologues series effective passivating agents. A mechanism that explains the trend in the anticorrosion activity of polyamines is proposed. © The Author(s) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…51,52 Gorantla et al and Karunaratne et al found that the polishing slurries consisting of En at alkaline pH were able to enhance the removal rate of Cu films. 53,54 Keeping these results in mind, we chose citric acid, glycine, EDTA, and En as the chelating agents in the cleaning solutions for our experiments.…”
Section: Choice Of Chelating Agent For Cleaning-various Reagents Havementioning
confidence: 99%
“…51,52 Gorantla et al and Karunaratne et al found that the polishing slurries consisting of En at alkaline pH were able to enhance the removal rate of Cu films. 53,54 Keeping these results in mind, we chose citric acid, glycine, EDTA, and En as the chelating agents in the cleaning solutions for our experiments.…”
Section: Choice Of Chelating Agent For Cleaning-various Reagents Havementioning
confidence: 99%
“…Dinusha P. et al 18 investigated the effect of linear aliphatic polyamines on copper removal rate in chemical mechanical planarization. It was revealed that the corrosion of copper can be controlled by changing the molecular weight of polyamine.…”
mentioning
confidence: 99%
“…17 Dinusha P. Karunaratne et al investigated the role of homologous linear aliphatic polyamines on copper removal rate. 18 They found that the corrosion of copper could be controlled by simply changing the molecular weight of the aliphatic polyamine. When the ultra-low-k materials are introduced as interlevel dielectrics, the copper slurry relies heavily on the z E-mail: luanyz1988@126.com chemical route by selecting special complexing agents to achieve a low down-pressure at a low concentration of BTA.…”
mentioning
confidence: 99%